NASD Rule 2711 and Changes in Analysts' Independence in Making Stock Recommendations - Chen, Chih-Ying; Chen, Peter F. (The Accounting Review, 2009)
ABSTRACT: This study provides evidence of changes in how analysts generate stock recommendations after the SEC's approval of NASD Rule 2711 in May 2002, which introduced regulatory reforms to enhance the independence of analysts' research. We investigate the relations of analysts' stock recommendations with intrinsic value estimates (based on analysts' earnings forecasts relative to the stock prices, V/P) and with investment-banking-related conflicts of interest during the 1994–2005 period. We find a stronger relation between analysts' stock recommendations and V/P and a weaker relation between analysts' stock recommendations and conflicts of interest in the post-Rule period than prior to the implementation of the Rule. Moreover, the increases in the relation between stock recommendations and V/P after the implementation of the Rule are greater for the stocks recommended by analysts with greater potential conflicts of interest. Our findings suggest that the implementation of Rule 2711 has enhanced analysts' independence.